IoT and LoRaWAN - Ashraf, Ahmed; Tanvir, Arif Raihan; A. Rashid, Rozeha; Abdul Hamid, Siti Zaleha; Johari, Zaharah; Abdul Rahim, Herlina; Mohamad, Elmy Johana (Penerbit UTHM, 2020)
The advancement in the field of digital communication and modern technology has introduced us the concept of IoT or simply Internet of Things. IoT has changed the way we do our daily works. Problems such as resource management, effects of globalization, environmental pollution are being handled pretty well with the IoT technology. All over the world billions of internets connected devices are used now a-days. As we advance with the IoT technology high power consumption and the short range of network servers are few issues that we have to face.